Molecular design and mathematical prediction in the creation of neuroprotectors with an antioxidant mechanism of action - Ryzhenko, V. P.; Belenichev, I. F.; Bak, P. G.; Ryzhov, A. A.; Риженко, Віктор Павлович; Бєленічев, Ігор Федорович; Бак, Павло Геннадійович; Рижов, Олексій Анатолійович (My University, 2019)
Vascular diseases of the brain - one of the leading causes of morbidity and mortality and disability in the population of the EU countries, the USA and Japan. Every year in the world suffer a stroke of about 6 million people. The increase in the prevalence of stroke seen in people of the working age - to 60 years. According to international EP and demiological studies, 4.7 million people die of stroke every year in the world. In most industrialized countries, stroke takes 2-3 place in the structure of total mortality of the population, second only to cardiovascular pathology. Early 30-day mortality after a stroke averages 30-40%, and about 50% of patients die within a year.